Error Handling Method for Improving BDS Monitoring Accuracy of Bridge Deformation - Longsheng Bao; Tianyang Tao; Ling Yu (Advances in Civil Engineering)
The existing high-tech bridge deformation monitoring technologies mostly use the GPS system. To eliminate the dependence on this system, China has independently developed and built the Beidou satellite navigation system. In this study, an improved algorithm for differently modulated signals is proposed to increase the accuracy of satellite monitoring and minimise the intercode interference into the output signals of the Beidou bridge deformation monitoring system. It includes a modified recurrent least square constant modulus algorithm (RLS-CMA) developed using MATLAB software. The numbers of iterations for four modulated signals are determined through various blind equalisation and intersymbol interference (ISI) algorithms as well as by performing error vector magnitude comparison simulations without equalisation, with CMA equalisation, and with enhanced RLS-CMA equalisation. At high signal-to-noise ratios, the correction speed and anti-intercode interference capability of the improved RLS-CMA are greater than those of the CMA. Moreover, the lower the error vector amplitude, the higher is the accuracy of received constellations. The error vector amplitude achieved by the RLS-CMA equalisation algorithm is lower than those of the CMA equalisation and nonequalisation algorithms, while its accuracy is increased by 17%. Hence, the improved RLS-CMA can eliminate ISI, increase the accuracy of satellite monitoring, and satisfy the requirements of theoretical analysis, calculation accuracy, and engineering error.